An experimental test of the impact of adolescent anxiety on parental sick role reinforcement behavior. (October 2018) - Bilsky, Sarah A.; Cloutier, Renee M.; Bynion, Teah-Marie; Feldner, Matthew T.; Leen-Feldner, Ellen W.
Abstract: A large body of work links parental sick role reinforcement behavior to adolescent panic vulnerability. To date, however, little work has examined the role of the adolescent in this process. The current study addressed this gap in the literature, using a novel method to experimentally test the impact of adolescent anxiety during a straw-breathing task on parental propensity to engage in sick role reinforcement behavior. An unselected sample of 51 early adolescents (26 female, 10–14 years) and their parents participated in the study. Adolescents were trained to mimic a straw-breathing task, and adolescent reactions to the task were scripted. Parents were randomly assigned to watch their adolescent react either a) anxiously or b) non-anxiously to the straw-breathing task. Parents who viewed their adolescent react anxiously ended the task earlier, reported that they would reinforce more sick role behavior, and reported more negatively valenced reactions during the task than parents who viewed their adolescent react non-anxiously to the task. No group differences emerged in terms of parental self-reported or physiological arousal during the task. Results suggest that adolescent anxiety increases parental sick role reinforcement behavior. Findings are discussed in terms of future directions for reducing parenting behaviors thought to increase vulnerability for panic among adolescents. Highlights: Adolescent anxiety during a straw breathing task is related to parental self reported and behavioral sick role reinforcement. Parents valence became more negative in response to adolescent anxious reactions to a straw breathing task. Parents did not evidence more self reported or physiological arousal in the presence of adolescent anxiety.